2020
DOI: 10.1097/tp.0000000000002958
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Japanese Survey Assessing the Long-term Outcomes of Liver Retransplantation Using Living Donor Grafts

Abstract: Background. Liver transplantation is the most suitable treatment option available for end-stage liver disease. However, some patients require retransplantation, despite medical advances that have led to improved survival. We aimed to compile a definitive, nationwide resource of liver retransplantation data in Japan, seeking to identify the predictors of patient survival posttransplantation. Methods. Questionnaires were sent to 32 institutions that had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 12 publications
3
34
1
Order By: Relevance
“…(9) In a nationwide retrospective survey from Japan, 123 adult liver and 142 pediatric liver retransplants were performed before 2015, of which living donor grafts were used in 194 (73%) patients. (10) The main indication for retransplantation was chronic rejection or disease recurrence, leading to a long average time interval of 1468 days between the first and second transplants. (10) Risk factors for worse outcomes included MELD scores >25, hospitalization at the time of retransplantation, and a time interval <365 days since the primary transplant.…”
Section: Brief Report | 889mentioning
confidence: 99%
See 1 more Smart Citation
“…(9) In a nationwide retrospective survey from Japan, 123 adult liver and 142 pediatric liver retransplants were performed before 2015, of which living donor grafts were used in 194 (73%) patients. (10) The main indication for retransplantation was chronic rejection or disease recurrence, leading to a long average time interval of 1468 days between the first and second transplants. (10) Risk factors for worse outcomes included MELD scores >25, hospitalization at the time of retransplantation, and a time interval <365 days since the primary transplant.…”
Section: Brief Report | 889mentioning
confidence: 99%
“…(10) The main indication for retransplantation was chronic rejection or disease recurrence, leading to a long average time interval of 1468 days between the first and second transplants. (10) Risk factors for worse outcomes included MELD scores >25, hospitalization at the time of retransplantation, and a time interval <365 days since the primary transplant. (10) As summarized by Au et al, successful LDLT in high-risk recipients requires the following 3 essential elements: (1) recognition of futility, (2) an optimized graft, and (3) experience.…”
Section: Brief Report | 889mentioning
confidence: 99%
“…The similar in-hospital mortality after liver re-transplantation between the high and low-volume centers in our study may partly be explained by the higher proportion of early liver re-transplantation in the low-volume centers compared to the high volume centers. The difference in outcome between early and late liver re-transplantation are still controversial as some studies suggest that early re-transplantation is associated with better survival [ 37 , 38 ], whereas others report that late re-transplantation may result in better outcome [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States of America, a study using Adult to Adult Living Donor Liver Transplantation Study (A2ALL) data collected between 1998 and 2014 revealed that 110 recipients (10.3%) of 1,065 patients underwent retransplantation, in which hepatitis C virus infection, longer length of stay, hepatic artery thrombosis, biliary stricture, infection, and disease recurrence were associated with increased risk of retransplantation [1]. In a Japanese multicenter study, 7,937 liver transplants had been performed at 67 institutions by the end of 2014, with 7,673 LD and 264 DD liver transplants [2]. First transplantation was performed in 7,682 patients (96.8%), second transplantation in 242 patients (3.0%), and third transplantation in 13 patients (0.2%) [2].…”
Section: Introductionmentioning
confidence: 99%
“…In a Japanese multicenter study, 7,937 liver transplants had been performed at 67 institutions by the end of 2014, with 7,673 LD and 264 DD liver transplants [2]. First transplantation was performed in 7,682 patients (96.8%), second transplantation in 242 patients (3.0%), and third transplantation in 13 patients (0.2%) [2].…”
Section: Introductionmentioning
confidence: 99%